3D planar velocity measurements, using Mach-Zehnder interferometric-filter-based planar Doppler velocimetry (MZI-PDV) and imaging fibre bundles - Lu, Z. H.; Charrett, Thomas O. H.; Ford, Helen D.; Tatam, Ralph P. (Cranfield University, 2008)
Three component planar flow-field measurements are made using imaging fibre bundles to port different views of the measurement plane, defined by a laser light sheet, to a single imaging head. The Doppler frequency shifts of light scattered by particles entrained in the flow are transduced to intensity variations using a Mach-Zehnder interferometric filter. The free spectral range of the filter can be selected by adjusting the optical path difference of the interferometer. This allows the velocity measurement range, sensitivity and resolution to be varied. Any laser wavelength may be used. A phase locking system has been designed to stabilise the interferometric filter.
Keywords: planar Doppler velocimetry; PDV; Mach-Zehnder interferometer; flow measurement; phase control